Energetics, energy availability and Relative Energy Deficiency in Sport (REDs) in female football players: Methodological perspectives and research implications - Dasa, M. S. (The Arctic University of Norway, 2024)
Background For athletes, it is imperative that energy intake (EI) adequately addresses the total energy requirements inherent to their specific sport. Low energy availability (LEA), which is the failure to provide the body with adequate energy to sustain homeostasis, may potentially result in Relative Energy Deficiency in Sport (REDs). This is a syndrome that can have detrimental health consequences, including altered menstrual, bone and endocrine functions. There is limited understanding of the energy requirements, as well as the prevalence and health consequences of LEA and REDs among female football players. Further, several methodological limitations in measuring EA impede the validity of findings. Considering this, the objective of this thesis was to explore the concepts of energetics, energy availability (EA) and REDs among female football players, with additional focus on methodological approaches.